2020
DOI: 10.1002/adma.201905640
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Plasmonic Chirality: Fundamentals and Applications

Abstract: Molecular chirality is a geometric property that is of great importance in chemistry, biology, and medicine. Recently, plasmonic nanostructures that exhibit distinct chiroptical responses have attracted tremendous interest, given their ability to emulate the properties of chiral molecules with tailored and pronounced optical characteristics. However, the optical chirality of such human‐made structures is in general static and cannot be manipulated postfabrication. Herein, different concepts to reconfigure the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 54 publications
(124 reference statements)
0
73
0
Order By: Relevance
“…Another unparalleled advantage of DNA origami for chiral assembly of metallic NPs is the reconfigurable capability under external physical or chemical stimuli., [183][184][185] which makes dynamic modulation of chiroptical activity possible by imparting reconfigurability and functionality to originally passive plasmonic systems. As shown in Figure 8e, a 3D plasmonic cross-like nanostructure consisting of two Au NRs can be created by hosting the NRs on a switchable DNA origami template made of two connected bundles.…”
Section: Chirality Transfer Via Dna-guided Self-assemblymentioning
confidence: 99%
“…Another unparalleled advantage of DNA origami for chiral assembly of metallic NPs is the reconfigurable capability under external physical or chemical stimuli., [183][184][185] which makes dynamic modulation of chiroptical activity possible by imparting reconfigurability and functionality to originally passive plasmonic systems. As shown in Figure 8e, a 3D plasmonic cross-like nanostructure consisting of two Au NRs can be created by hosting the NRs on a switchable DNA origami template made of two connected bundles.…”
Section: Chirality Transfer Via Dna-guided Self-assemblymentioning
confidence: 99%
“…Importantly, it was found that optical helicity density fundamentally determines the circular dichroism (CD) in local interactions of light with chiral molecules or nanostructures 45 , which is critical for the characterization of chiral molecules in important biochemistry and pharmaceutical industries 46 , 47 . Therefore, the realization of on-chip and active modulation on optical helicity density and the associated CD is of great significance 48 , 49 . To this aim, an array of three-arm pinwheels are designed and the induced helicity enhancement factor is evaluated by , where η and η 0 are the calculated optical helicity density with and without the nanostructure, respectively, under left-/right-handed circularly polarized (LCP/RCP) incidence (see “Methods” for details) 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The DNA origami template can exhibit tunable relative rotation angles between two plasmonic achiral nanorods, allowing distinct optical chiral responses, as illustrated in Figure 3D. Beyond DNA technologies [71], many other techniques can be used to reconfigure the strong optical chirality of these meta-atoms, including hydrogenation/dehydrogenation [72,73], photoexcitation [74], and others [75][76][77].…”
Section: Full-wave Manipulation Via Stacked Meta-atomsmentioning
confidence: 99%